The Impact of Financial Financing on the Future of the Iraqi Print Press, A Survey Study by the Contactor - qusai majeed, Rand; waheed Faidhi, Anmar (ALBAHITH ALALAMI, 2021)
The objectives of this study revolve around identifying the extent of funding impact on the future of the printed Iraqi press, and whether it threatens their chances of survival, stating the extent of technological development on the income of the printed newspaper, and identifying the causes of the financial crisis on the newspaper. This research is classified as descriptive research, and the researcher used the survey method, and adopted the questionnaire of the views of the contactors, in five Iraqi newspapers (morning - extent - time - the way of the people - the call). The research community included (68) respondents, whereby the comprehensive inventory method was used to define the research community, and the researcher used to collect information research tools (questionnaire form) and (source interview). The research reached a number of conclusions, the most important of which are: 1- Most of the printed press organizations suffer from financing problems, and the volume of funding. Not compatible with the cost of issuing a single issue. 2- The financial crisis experienced by the press as a result of lack of funding and the absence of advertisements, in addition to the lack of distribution of newspaper copies and the emergence of the electronic press. 3- Most of the press organizations have dismissed a number of journalists to face the financial crisis they are facing. 4- Newspapers do not adopt an independent policy without the influence of the funding agency in processing the news. 5-There are indicators for dispensing paper publications and restricting them to digital copies.